Deskripsi Pemahaman Konsep Fungsi - Yusran, Muhammad (JURNAL NALAR PENDIDIKAN, 2017)
AbstractThe purpose of this research is to describe the comprehending of concepts of functions of the students, with instrument test the ability of mathematics and interviews. The focus of this research is to describe the students understanding about concepts of functions. The subject of the research are the three students of grade XI SMAN 3 Pangkajene. The results of this research showed: (1) about understanding of definition of function, but student has not yet been able to stated the concept that are understood. (2) Understanding of functions related to determines the value of function, domain, codomain, and range of a function, the students can name the domain, codomain and range of the function presented in the form of the arrow diagram but it is very wrong if it presented in another form. (3) The students' understanding of the concept of function composition, two of the three subjects mistaken in understanding the concept of function composition, students consider the function composition as same as the substitution while the other students declare the composition equal to the multiplication of the function. (4) Students can not relate the concept of inverse functions that understood to each other, it is even found that students assume the function derivative is the same as the inverse of that function.Keywords: Composition and invers function, Descriptions of comprehending concepts, FunctionsAbstrakPenelitian ini bertujuan mendeskripsikan pemahaman konsep fungsi siswa, dengan instrumen tes kemampuan matematika dan wawancara. Fokus penelitian yaitu mendeskripsikan pemahaman siswa terkait konsep fungsi. Subjek penelitian adalah tiga orang siswa kelas XI SMAN 3 Pangkajene. Hasil penelitian menunjukkan: (1) terkait pemahaman defenisi fungsi, siswa belum mampu menyatakan ulang konsep yang dipahaminya. (2) Pemahaman fungsi terkait menentukan nilai fungsi, domain, kodomain, dan range suatu fungsi, siswa dapat menyebutkan domain, kodomain dan range untuk fungsi yang disajikan dalam bentuk diagram panah tetapi sangat keliru jika disajikan dalam bentuk yang lain. (3) Pemahaman siswa terkait konsep komposisi fungsi, dua dari tiga subjek keliru dalam menahami konsep komposisi fungsi, siswa menganggap komposisi fungsi sama dengan subtitusi sedangkan siswa yang lain menyatakan komposisi sama dengan perkalian fungsi. (4) Siswa tidak dapat mengaitkan konsep fungsi invers yang dipahami satu sama lain, bahkan ditemukan bahwa siswa menganggap turunan fungsi sama dengan invers fungsi tersebut.Kata Kunci: Fungsi komposisi invers, Deskripsi pemahaman konsep, Fungsi